Parallel Activin and BMP signaling coordinates R7/R8 photoreceptor subtype pairing in the stochastic Drosophila retina - Wells, Brent S (eLife, 2017)
Drosophila color vision is achieved by comparing outputs from two types of color-sensitive photoreceptors, R7 and R8. Ommatidia (unit eyes) are classified into two subtypes, known as ‘pale’ or ‘yellow’, depending on Rhodopsin expression in R7 and R8. Subtype specification is controlled by a stochastic decision in R7 and instructed to the underlying R8. We find that the Activin receptor Baboon is required in R8 to receive non-redundant signaling from the three Activin ligands, activating the transcription factor dSmad2. Concomitantly, two BMP ligands activate their receptor, Thickveins, and the transcriptional effector, Mad. The Amon TGFβ processing factor appears to regulate components of the TGFβ pathway specifically in pale R7. Mad and dSmad2 cooperate to modulate the Hippo pathway kinase Warts and the growth regulator Melted; two opposing factors of a bi-stable loop regulating R8 Rhodopsin expression. Therefore, TGFβ and growth pathways interact in postmitotic cells to precisely coordinate cell-specific output.